TSC2-mutated perivascular epithelioid cell tumor with partial response to mTOR inhibition: a case report and literature review - Xiaopeng Suo; Ruihan Dong; Lingling Zhang; Xiaoying Zhang; Xiangji Li; Mengmeng Xiao (Discover Oncology)
Abstract Perivascular epithelioid cell tumors (PEComas), rare mesenchymal neoplasms with heterogeneous behavior, are molecularly characterized by TSC2 inactivation driving mammalian target of rapamycin (mTOR) pathway activation. We present a typical case of a 63-year-old female with metastatic high-grade PEComa featuring a TSC2 mutation (68.57% VAF) and elevated tumor mutational burden (19.7 mut/Mb), manifesting as peritoneal carcinomatosis and pulmonary metastases. Everolimus therapy following multidisciplinary assessment induced a radiologically confirmed partial response within 4.5 months with sustained clinical benefit. This outcome validates mTOR inhibition in TSC2-mutated PEComas and underscores the imperative of molecular profiling in mesenchymal tumor management. The significant mutational burden suggests potential immunotherapy responsiveness, informing future combination strategies. These findings emphasize molecularly guided precision approaches in rare malignancies and warrant systematic exploration of therapeutic sequencing and resistance mechanisms in mTOR-driven tumors.